Chromatin structure and 3D architecture define the differential functions of PU.1 regulatory elements in blood cell lineages - Kevin Qiu; Duc C. Vu; Leran Wang; Nicholas N. Nguyen; Anna K. Bookstaver; Katia Sol-Church; Hui Li; Thang N. Dinh; Adam N. Goldfarb; Daniel G. Tenen; Bon Q. Trinh (Epigenetics & Chromatin)
Abstract The precise spatiotemporal expression of the hematopoietic ETS transcription factor PU.1, a key determinant of hematopoietic cell fates, is tightly regulated at the chromatin level. However, how chromatin signatures are linked to this dynamic expression pattern across different blood cell lineages remains uncharacterized. Here, we performed an in-depth analysis of the relationships between gene expression, chromatin structure, 3D architecture, and trans-acting factors at PU.1 cis-regulatory elements (PCREs). By identifying phylogenetically conserved DNA elements within chromatin-accessible regions in primary human blood lineages, we discovered multiple novel candidate PCREs within the upstream region of the human PU.1 locus. A subset of these elements localizes within an 8-kb-wide cluster exhibiting enhancer features, including open chromatin, demethylated DNA, enriched enhancer histone marks, present enhancer RNAs, and PU.1 occupation, presumably mediating PU.1 autoregulation. Importantly, we revealed the presence of a common 35-kb-wide CTCF-flanked insulated neighborhood that contains the PCRE cluster (PCREC), forming a chromatin territory for lineage-specific and PCRE-mediated chromatin interactions. These include functional PCRE-promoter interactions in myeloid and B cells that are absent in erythroid and T cells. By correlating chromatin structure and 3D architecture with PU.1 expression in various lineages, we were able to attribute enhancer versus silencer functions to individual elements. Our findings provide mechanistic insights into the interplay between dynamic chromatin structure and 3D architecture in the chromatin regulation of PU.1 expression. This study lays crucial groundwork for additional experimental studies that validate and dissect the role of PCREs in epigenetic regulation of normal and malignant hematopoiesis.